2020
DOI: 10.1002/cbic.202000102
|View full text |Cite
|
Sign up to set email alerts
|

Surface Display of Complex Enzymes by in Situ SpyCatcher‐SpyTag Interaction

Abstract: The display of complex proteins on the surface of cells is of great importance for protein engineering and other fields of biotechnology. Herein, we describe a modular approach, in which the membrane anchor protein Lpp‐OmpA and a protein of interest (passenger) are expressed independently as genetically fused SpyCatcher and SpyTag units and assembled in situ by post‐translational coupling. Using fluorescent proteins, we first demonstrate that this strategy allows the construct to be inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…OMVs have proven their value in the development of a vaccine against Neisseria meningitis and are increasingly investigated as a vaccine against other pathogens [15]. Furthermore, the use of engineered OMVs has emerged as vehicles for targeted drug delivery [11]. In this article, it was shown that OMVs can serve as an in vivo immobilization strategy for recombinant production of self-sufficient CYP monooxygenases, thereby proposing an alternative production strategy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…OMVs have proven their value in the development of a vaccine against Neisseria meningitis and are increasingly investigated as a vaccine against other pathogens [15]. Furthermore, the use of engineered OMVs has emerged as vehicles for targeted drug delivery [11]. In this article, it was shown that OMVs can serve as an in vivo immobilization strategy for recombinant production of self-sufficient CYP monooxygenases, thereby proposing an alternative production strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, a recent article reports the display of CYP102A1 by in situ SpyCatcher-SpyTag interaction. [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SpyTag/SpyCatcher system has been used to immobilize foreign proteins onto nanoparticles 25 27 and bacterial outer membrane vesicles 25 30 . Recently, cell surface display of enzymes in E. coli using SpyTag/SpyCatcher has been reported 31 , but there was no example of displaying fusion proteins produced by post-translational ligation in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%